Pemahaman Etika Komunikasi Islam Terhadap Moralitas Pengguna Media Sosial - Amirah Jilan Fakhira; Marlya Fatira (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
This article describes the Comprehension of Islamic Communication Ethics on the Morality of Social Media Users in Muslim students majoring in Accounting at the Medan State Polytechnic. The data analysis technique used is linear regression analysis using quantitative methods. The data collection technique used a questionnaire distributed to 76 respondents via a google form. The indicators used in the independent variables are six principles of Islamic communication ethics and the dependent variable in the form of akhlakul karimah and akhlakul mazmumah. The results of this study indicate that the understanding of Islamic communication ethics has a partial effect on the morality of social media users